Risk of Seizures Following DTP and MMR Vaccines - J Gordon Millichap (Pediatric Neurology Briefs)
The risk of a first seizure, subsequent seizures, and neurodevelopmental disability following the administration of diphtheria and tetanus toxoids and whole-cell pertussis (DTP) vaccine and measles, mumps, and rubella (MMR) vaccine was studied by a retrospective review of children’s medical records at four health maintenance organizations, including University of Washington, Seattle; and Kaiser Permanente Groups in OR and CA, members of the CDC & P Vaccine Safety Datalink Project.